The Colors of Sports Organization Fringe Benefit in Malaysia - Kamarulzaman, Rashidah; Abd Rahim, Zulkiflee; Dzarr Muhammad Rus, Abu; Poniran, Halimi; Reza Abdul Ghoni, Mohd; Ali, Azlan; Iqbal Hussain, Hafezali (International Journal of Engineering and Technology, 2018)
Fringe benefit is a tool to retain an employees and a factor that contribute to job satisfaction. Wondering this issue, a study was conducted to determine the relationship between the types of fringe benefit and job satisfaction in a sports organization. A total of 100 respondents were selected from the National Sports Council of Malaysia to become the respondents for this study. Questionnaire method was used for data collection by using purposive random sampling. The finding shows, job satisfaction has a positive relationship with the pension plan, allowance, flexible working hours and vacation pay. In addition, flexible working hour and allowance were the dominant types of fringe benefit to achieve job satisfaction among the employees of the National Sports Council of Malaysia. The implication of this study indicates that non monetary and monetary types of fringe benefit influence the job satisfaction.Â Â